2016
DOI: 10.1080/2162402x.2016.1169356
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification augments the immunogenicity of human leukocyte antigen G serving as a tumor antigen for T cell-based immunotherapy

Abstract: (2016) Epigenetic modification augments the immunogenicity of human leukocyte antigen G serving as a tumor antigen for T cell-based immunotherapy, OncoImmunology, 5:6, e1169356 ABSTRACTTumor immune escape has been a major problem for developing effective immunotherapy. The human leukocyte antigen G (HLA-G) is a non-classical MHC class I molecule whose primary function is to protect the fetus from the mother's immune system. While HLA-G is hardly found in normal adult tissues, various tumor cells are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…In this context, a large body of research has demonstrated that blockade of HLA‐G and ILTs could restore the cytotoxicity of NK cells . For T cells, HLA‐G‐derived peptides HLA‐G 146–154 and HLA‐G 26–40 could effectively induce peptide‐specific CD8 + T cytotoxicity and tumor‐reactive CD4 + T‐cell responses, respectively, rendering the possibility of HLA‐G peptide‐based tumor immunotherapy . Finally, targeting tumor‐specific HLA‐G to develop drug delivery systems has been carried out.…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a large body of research has demonstrated that blockade of HLA‐G and ILTs could restore the cytotoxicity of NK cells . For T cells, HLA‐G‐derived peptides HLA‐G 146–154 and HLA‐G 26–40 could effectively induce peptide‐specific CD8 + T cytotoxicity and tumor‐reactive CD4 + T‐cell responses, respectively, rendering the possibility of HLA‐G peptide‐based tumor immunotherapy . Finally, targeting tumor‐specific HLA‐G to develop drug delivery systems has been carried out.…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 99%
“…75 For T cells, HLA-G-derived peptides HLA-G 146-154 and HLA-G [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] could effectively induce peptidespecific CD8 + T cytotoxicity and tumor-reactive CD4 + T-cell responses, respectively, rendering the possibility of HLA-G peptide-based tumor immunotherapy. 76,77 Finally, targeting tumor- specific HLA-G to develop drug delivery systems has been carried out. An HLA-G antibody conjugated to the surface of methotrexate (MTX)loaded nanobubbles (mAb HLA-G /MTX/PLGA NBs) could be specifically transported to the HLA-Gpositive choriocarcinoma cancer cells JEG-3 in vitro and tumor tissues in vivo in a tumor-bearing murine model of BALB/c (nu/nu) nude mice established with JEG-3 cells.…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 99%
“…Expression levels of HLA-G increase in BC,21 which associates with poor prognosis 22. Following studies on a 14 bp InDel polymorphism in the HLA-G gene, Haghi et al performed genotyping and found that patients with higher BC stages had a higher frequency of allele deletion compared with patients with lower stages, indicating that the 14 bp InDel polymorphism in the HLA-G gene was a risk factor for the development of BC 23.…”
Section: Tumor-related Immune Evasionmentioning
confidence: 99%
“…One peptide, HLA-G 146–154 , was observed to effectively induce peptide-specific CTLs and these exhibited cytotoxic activity against HLA-G-expressing HLA-A24-positive renal cell carcinoma cells [109]. Furthermore, a recent study showed that a MHC class II-binding peptide, HLA-G 26–40 , was effective in eliciting a tumor-reactive CD4 + T cell response [110]. It will be interesting in the future to explore the opportunities for modulating HLA-G expression in melanoma tumor cells and other tumors or induce an HLA-G peptide-specific immune response as new innovative cancer immunotherapy.…”
Section: Hla-g In Malignant Melanoma: a Role For Cancer Immune Thementioning
confidence: 99%